Factor H Family Proteins in Complement Evasion of Microorganisms - Józsi, Mihály (Frontiers in Immunology, 2017)
Human-pathogenic microbes possess various means to avoid destruction by our immune system. These include interactions with the host complement system that may facilitate pathogen entry into cells and tissues, expression of molecules that defuse the effector complement components and complexes, and acquisition of host complement inhibitors to down-regulate complement activity on the surface of the pathogen. A growing number of pathogenic microorganisms have acquired the ability to bind the complement inhibitor factor H from body fluids and thus hijack its host protecting function. In addition to factor H, binding of factor H-related proteins was also demonstrated for several microbes. Initial studies assumed that these proteins are complement inhibitors similar to factor H. However, recent evidence suggest that factor H-related proteins may rather enhance complement activation both directly and also by competing with the inhibitor factor H for binding to certain ligands and surfaces. This mini review focusses on the role of the main alternative pathway regulator factor H in host-pathogen interactions, as well as on the emerging role of the factor H-related proteins as enhancers of complement activation.